1980
DOI: 10.1126/science.7001627
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Conformation of Luteinizing Hormone-Releasing Hormone: Evidence from a Conformationally Constrained Analog

Abstract: An analog of luteinizing hormone-releasing hormone containing a gamma-lactam as a conformational constraint has been prepared with the use of a novel cyclization of a methionine sulfonium salt. The analog is more active as a luteinizing hormone-releasing hormone agonist that the parent hormone, and provides evidence for a bioactive conformation containing a beta-turn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
163
0
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(169 citation statements)
references
References 19 publications
5
163
0
1
Order By: Relevance
“…Over the past 5 years there has been an escalating need for synthetic peptides in a wide variety of applications, including the development of synthetic peptide vaccines (1)(2)(3)(4)(5), the detailed study of antigen-antibody interactions (6)(7)(8)(9)(10)(11), the preparation of optimal analogs of biologically active peptides (12)(13)(14), the optimization of peptide antigens of clinical diagnostic utility (15)(16)(17), the mapping of protein products of brain-specific genes (18,19), and the study of protein conformational parameters (20). In the majority of these studies, the limiting factor has been the availability and cost of the desired peptides.…”
mentioning
confidence: 99%
“…Over the past 5 years there has been an escalating need for synthetic peptides in a wide variety of applications, including the development of synthetic peptide vaccines (1)(2)(3)(4)(5), the detailed study of antigen-antibody interactions (6)(7)(8)(9)(10)(11), the preparation of optimal analogs of biologically active peptides (12)(13)(14), the optimization of peptide antigens of clinical diagnostic utility (15)(16)(17), the mapping of protein products of brain-specific genes (18,19), and the study of protein conformational parameters (20). In the majority of these studies, the limiting factor has been the availability and cost of the desired peptides.…”
mentioning
confidence: 99%
“…This approach has previously provided insight into the conformation-activity relationships of several naturally occurring linear and cyclic peptide hormones, including the enkephalins (13), luteinizing hormone-releasing hormone (14), somatostatin (15), oxytocin (16)(17)(18), vasopressin (18,19), and bradykinin (20). Based on our earlier reports of the exceptional in vitro (11) and in vivo (21) biological properties of [Nle4,DPhe7]-a-MSH on both normal and transformed melanophores, the evaluation of possible secondary structures (22) in a-MSH, the known conformational effect of introducing D-amino acids into peptides (23,24), and examination of three-dimensional molecular models of this stereoisomeric analogue, we concluded that a ,B-turn or other peptide chain-reversal region within the central active site (His-Phe-Arg-Trp) of a-MSH might be functionally related to its biologically active conformation.…”
mentioning
confidence: 99%
“…This observation led to the suggestion that -turns may serve as sites for molecular recognition. 3,4 Moreover, turns in peptides and proteins have been frequently suggested to be the bioactive conformations [5][6][7][8][9][10][11] involved in receptor binding, immune recognition, posttranslational modifications, and other processes. 12 Since turns are the shortest relatively stable and ordered structural elements, it has been proposed that they act as nucleation sites in the process of protein folding.…”
Section: Introductionmentioning
confidence: 99%